Sleep duration and risk of cardio-cerebrovascular disease: A dose-response meta-analysis of cohort studies comprising 3.8 million participants - Huang, Yi-Ming; Xia, Wei; Ge, Yi-Jun; Hou, Jia-Hui; Tan, Lan; Xu, Wei; Tan, Chen-Chen (Frontiers in Cardiovascular Medicine, 2022)
Background The effect of extreme sleep duration on the risk of cardiovascular and cerebrovascular diseases (CCDs) remains debatable. The pathology of CCDs is consistent in some respects (e.g., vascular factors), suggesting that there may be an overlapping range of sleep duration associated with a low risk of both diseases We aimed to quantify the dose-response relationship between sleep duration and CCDs. Study objective To explore whether there is an optimal sleep duration (SD) in reducing the risk of CCDs. Methods PubMed and EMBASE were searched until June 24, 2022 to include cohort studies that investigated the longitudinal relationships of SD with incident CCDs, including stroke and coronary heart disease (CHD). The robusterror meta-regression model (REMR model) was conducted to depict the dose-response relationships based on multivariate-adjusted risk estimates. Results A total of 71 cohorts with 3.8 million participants were included for meta-analysis, including 57 for cardiovascular diseases (CVD) and 29 for cerebrovascular disease. A significant U-shaped relationship was revealed of nighttime sleep duration with either cardiovascular or cerebrovascular disease. The nighttime sleep duration associated with a lower risk of CVD was situated within 4.3–10.3 h, with the risk hitting bottom at roughly 7.5 h per night (pnon–linearity < 0.0001). Sleep duration associated with a lower risk of cerebrovascular diseases ranges from 5 to 9.7 h per night, with the inflection at 7.5 h per night (pnon–linearity = 0.05). Similar non-linear relationship exited in daily sleep duration and CCDs. Other subgroup analyses showed non-linear relationships close to the above results. Conclusion Rational sleep duration (7.5 h/night) is associated with a reduced risk of cardio-cerebrovascular disease for adults.